Investigation of metallic glass as thermal absorption layer for laser thermal lithography - Wong, Hsien Han. (2010)
A study on the feasibility of using the metallic glass AlNiGd as an absorption layer for laser thermal lithography was done. From characterisation experiments done, it was found that metallic glasses have the phase change properties required to be used as a recording layer in rewritable optical discs. Using this phase change property to control the heat profile of the absorption layer irradiated by laser, patterns can be formed on a dielectric layer that was deposited above it by means of selective etching. This ability to create patterns allows laser thermal lithography to be used in DVD-ROM mastering process.